2011
DOI: 10.1177/160940691101000206
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Reflection on the Use of Translators/Interpreters in a Qualitative Cross-Language Research Project

Abstract: Based on experiences from a qualitative research project on immigrant women's English language acquisition, we critiqued the traditional positivist model, and identified a number of issues related to the engagement of translators/interpreters in feminist and community-based research. The issues that we identified amount to serious questions about ambiguities and ownership of translated language content; assumptions about community familiarity and cultural similarity between researchers, translators, and partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 24 publications
0
60
0
Order By: Relevance
“…Other researchers have suggested that sharing a similar background helps participants build better rapport with the interviewers and increases the likelihood of discussing sensitive topics more openly [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have suggested that sharing a similar background helps participants build better rapport with the interviewers and increases the likelihood of discussing sensitive topics more openly [22]. …”
Section: Discussionmentioning
confidence: 99%
“…These outcomes included relevant research development and effective participant recruitment (Halkoaho et al, 2016;Liamputtong, 2008;Spector, 2012;Wallin & Ahlström, 2006), advocacy of the research on the value of the project to the broader community (Lee, Sulaiman-Hill, & Thompson, 2014;Spector, 2012), and guidance with language and cultural sensitivities (Berman & Tyyskä, 2011;Lantz, Viruell-Fuentes, Israel, Softley, & Guzman, 2001;Lee, Sulaiman-Hill, & Thompson, 2014). Of specific importance to our project, the brokers already knew each participant through their service provider-client relationships.…”
Section: Positive Outcomes Of Working With the Brokersmentioning
confidence: 99%
“…The interpreters made it possible to communicate with study participants (Squires, 2008), served as cultural ambassadors (Berman, 2011;Edwards, 1998;Hennings, Williams, & Haque, 1996;Shklarov, 2007), and organized logistics for travel and interview locations.…”
Section: Finding An Interpreter: the Partnership Beginsmentioning
confidence: 99%